2005
DOI: 10.3201/eid1105.041225
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Risk Perception, Hong Kong

Abstract: A telephone survey of 986 Hong Kong households determined exposure and risk perception of avian influenza from live chicken sales. Householders bought 38,370,000 live chickens; 11% touched them when buying, generating 4,220,000 exposures annually; 36% (95% confidence interval [CI] 33%–39%) perceived this as risky, 9% (7%–11%) estimated >50% likelihood of resultant sickness, whereas 46% (43%–49%) said friends worried about such sickness. Recent China travel (adjusted odds ratio 0.35; CI 0.13–0.91), traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 25 publications
11
105
2
4
Order By: Relevance
“…Studies For each categorical variable, odds for willingness to take health risks in a given category were calculated relative to the reference category. CI confidence intervals on risk perception related to infectious diseases such as SARS and avian influenza and their relation with precautionary behaviors in general, have shown great variation between countries both in perceptions and behaviors [7,22]. The results about the younger age and the willingness to take health risks especially on holidays are in line with the studies showing that younger people especially take more health risks while traveling, e.g., by neglecting protecting hygienic measures, and behave in general in a more hedonistic way than they normally do [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies For each categorical variable, odds for willingness to take health risks in a given category were calculated relative to the reference category. CI confidence intervals on risk perception related to infectious diseases such as SARS and avian influenza and their relation with precautionary behaviors in general, have shown great variation between countries both in perceptions and behaviors [7,22]. The results about the younger age and the willingness to take health risks especially on holidays are in line with the studies showing that younger people especially take more health risks while traveling, e.g., by neglecting protecting hygienic measures, and behave in general in a more hedonistic way than they normally do [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that travel clinic consultations can improve adherence, e.g., to malaria prophylaxis [6]. Awareness of, e. g., the avian influenza risk among the populations in the epidemic areas could also be improved [7].…”
Section: Introductionmentioning
confidence: 99%
“…in Phase 3.The persons who slaughter, farm, rear, transport, sell and who are closely related with poultry are considered as high risk areas (Xiang et al, 2010). The presence in the household of dead or sick poultry acts as a risk factor (Fielding et al, 2005). For the purpose of controlling AI a sound communication channel is a burning question to set up.…”
Section: S K Sarker and Othersmentioning
confidence: 99%
“…Although pandemics range from mild to very severe, in contemporary societies infectious diseases, even in 'far-flung' places, quickly come to the attention of an international audience (Joffe & Haarhoff, 2002). Modern travel, and mass transportation, means that human-transmittable influenzas may take only days to travel worldwide (Fielding, Lam, Ho, Lam, Hedley & Leung, 2005;Washer, 2004). The deaths of normally 'healthy' people can shock both professionals and the lay public (Sim & Mackie, 2009).…”
Section: Introductionmentioning
confidence: 99%